Strategic patterns and firm performance: comparing consistent, flexible and reactor strategies. Issue 7 (13th November 2017) - Anwar, Jamil; Hasnu, SAF
Abstract : Purpose: Firms face the paradox of adapting change and remaining stable to control uncertainty simultaneously to maintain their competitive position because both aspects are essential for the firm's effectiveness. This has raised a debate in the contemporary literature that whether firms should remain consistent or adapt flexibility in their strategic choice to produce better performance? The supporters of both the arguments provide substantial evidence in their favor. The purpose of this paper is to investigate the strategy-performance relationship in this context along with contingent effect of firm size and industry. Design/methodology/approach: Empirical analysis using seven years financial data of 307 joint stock firms from 12 industries is done by applying Miles and Snow strategic typology. Scoring method is used to classify the strategic orientation of the firms. Univariate and multivariate regression models are applied to investigate the influence of strategy, firm size, and industry on firm performance both individually and collectively. Findings: The results show that most of the firms in Pakistan are consistent in their strategic stance (43 percent) followed by flexible (40 percent) and reactors (17 percent). The mean differences in the performance of consistent, flexible, and reactor strategies show that both consistent and flexible strategies performed equally well and outperformed the reactors. However, there is significant variation in the performance of the strategic types due to the variation in firm size and industries whereas the contingent effect of firm size, industry, and strategy is statistically insignificant. Originality/value: The methodology used for the identification of transition of strategic stance of the firms over time to know the consistent, flexible, and reacting behavior of the firms from archived data is the important contribution to the literature. The methodology can be replicated in longitudinal studies for identification of strategic groups in typological research.